Peer Violence and Gender in the Grammar School Social and Cultural Contexts - Iwona Chmura-Rutkowska (University of Lower Silesia, 2013)
In this text, I focus on the role that dominant culturally based gender stereotypes and beliefs play in adolescent violence in the context of everyday school life. In other words, I concentrate on how the androcentric order, unequal social position of women and men, and cultural definitions of femininity and masculinity impact everyday school reality and the relationships between adolescent girls and boys. The text builds on the notion of gender understood as a changeable and socially negotiable cultural construct that plays out in discourses, definitions, values and norms concerning femininity, masculinity and the differences between them.